LITERATURE REVIEW: DETERMINANT FACTORS OF MEDICATION CONTROL COMPLIANCE IN HYPERTENSION PATIENTS IN INDONESIA - Rahma Dina, Elsa; Cahyani Putri, Gita; Fakhrunnisa, Najwa; Syifa Urrahma Fauzi, Raifa; Nur Amalina, Nindya; Maraditha, Jeanice; Rifazuli, Aissa; Yonisa putra, Al-Gheni (Pharmacy Program, Faculty of Medicine, UPN Veteran Jakarta, 2024)
Hypertension is a type of cardiovascular disease with a prevalence that continues to increase every year and is a global cause of death, especially among the elderly. The World Health Organization (WHO) notes that approximately 1.13 billion people worldwide live with hypertension. One of the major challenges in its management is low patient adherence to medication therapy, which impacts blood pressure control and increases the risk of complications. The level of non-adherence is caused by several internal and external factors. This research method uses a systematic literature review approach to examine the effect of patient knowledge level on compliance in hypertension treatment control. Literature was searched using Google Scholar with the inclusion criteria of relevant articles published in the range of 2015-2025, resulting in one main article and five supporting articles. The results showed that non-compliance is often caused by low patient knowledge, limited access to health services, advanced age, and socio-economic conditions. Patients who have a good understanding of hypertension and regularly follow medication and patient control tend to show better blood pressure control, so strategies related to education and more support are needed to improve patient compliance. Therefore, to improve adherence, an approach of continuous education, counseling, and support from health workers and families is needed. These strategies are important to prevent long-term complications and improve the quality of life of hypertensive patients